1064 nm Nd:YAG laser light affects transmembrane mitochondria respiratory chain complexes. Issue 9 (19th June 2019) - Ravera, Silvia; Ferrando, Sara; Agas, Dimitrios; De Angelis, Nicola; Raffetto, Mirco; Sabbieti, Maria G.; Signore, Antonio; Benedicenti, Stefano; Amaroli, Andrea
Abstract: Photobiomodulation (PBM) is a non‐plant‐cell manipulation through a transfer of energy by means of light sources at the non‐ablative or thermal intensity. Authors showed that cytochrome‐c‐oxidase (complex IV) is the specific chromophore's target of PBM at the red (600‐700 nm) and NIR (760‐900 nm) wavelength regions. Recently, it was suggested that the infrared region of the spectrum could influence other chromospheres, despite the interaction by wavelengths higher than 900 nm with mitochondrial chromophores was not clearly demonstrated. We characterized the interaction between mitochondria respiratory chain, malate dehydrogenase, a key enzyme of Krebs cycle, and 3‐hydroxyacyl‐CoA dehydrogenase, an enzyme involved in the β‐oxidation (two mitochondrial matrix enzymes) with the 1064 nm Nd:YAG (100mps and 10 Hz frequency mode) irradiated at the average power density of 0.50, 0.75, 1.00, 1.25 and 1.50 W/cm 2 to generate the respective fluences of 30, 45, 60, 75 and 90 J/cm 2 . Our results show the effect of laser light on the transmembrane mitochondrial complexes I, III, IV and V (adenosine triphosphate synthase) (window effects), but not on the extrinsic mitochondrial membrane complex II and mitochondria matrix enzymes. The effect is not due to macroscopical thermal change. An interaction of this wavelength with the Fe‐S proteins and Cu‐centers of respiratory complexes and with the water molecules could be supposed. Abstract : 1064 nm Nd:YAG laser light affects the transmembrane mitochondrial complexes I, III, IV and V (adenosine triphosphate synthase) activities, but not those of the extrinsic mitochondrial membrane complex II and mitochondria matrix enzymes, such as malate dehydrogenase and 3‐hydroxyacyl‐CoA dehydrogenase. The effect is not due to macroscopical thermal change but probably by an interaction of this wavelength with the Fe‐S proteins and Cu‐centers of respiratory complexes and changes of membrane fluidity.